USING DIGITAL PLATFORMS AND ONLINE COURSES IN TEACHING LEGAL DISCIPLINES (Journal of actual problems of jurisprudence, 2025)
This article provides a scientific analysis of the possibilities for effective use of digital platforms and online courses in the teaching of legal disciplines. The study analyzes the advantages and disadvantages of digital learning within the framework of teaching legal disciplines, and also examines the possibilities for effective integration of online courses into the modern educational process. In addition, the content and structure of online courses used in teaching legal disciplines are analyzed, and the impact of digitalization of the educational process on the study of these subjects is examined. The results of the analysis showed that digital platforms not only increase the accessibility of education but also significantly influence the development of students' digital competencies. Online courses allow students to study legal situations in a convenient format, and digital technologies provide an individual approach to learning, contributing to adaptation to the individual needs of students. Thus, during the study, a number of problems were identified, including the need to modernize teaching methods, improve digital literacy of teachers and students, and ensure effective mechanisms for assessing knowledge. In conclusion, the study defines the importance of a blended learning model that combines traditional and digital teaching methods in creating a flexible educational environment aimed at improving students' learning outcomes. Based on the research results, scientifically substantiated recommendations are developed for the effective use of online courses in the teaching of legal disciplines.Keywords: education, higher education, digital education, legal disciplines, educational technologies, digital platforms, online courses, massive Open Online Courses (MOOCs)